ASSESSMENT OF THE CONDITION OF THE GIRIMUKTI-JATIMULYA ROAD SECTION USING THE SDI (SURFACE DISTRESS INDEX) IN MAJALENGKA REGENCY - Fitra Sunandar; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2024)
The road is an important means of land transportation that is often used in various countries including Indonesia. In Indonesia, the road itself is an important land transportation infrastructure for people's lives in meeting the needs of life and earning a living. Lately, in 2023, road conditions in Indonesia are being criticized through various social media for about the many damaged road conditions, including on provincial authority roads and in district authority areas in Indonesia, including Majalengka Regency. Girimukti-Jatimulya road section is a road section authorized by Majalengka Regency which has a length of 1.7 km located in Kasokandel District as an alternative road section from Majalengka City Road Center to Cirebon-Bandung Provincial Road. So this study was conducted to determine the condition of the Girimukti-Jatimulya road section using the SDI (Surface Distress Index) method research. In this study, it was divided into 9 segments each length of each segment 200 m. The data is to be surveyed directly from the field using the SDI method assessment in the form of damage to the crack area, crack width, number of holes, and wheel marks. The results of direct surveys from the field have been recapitulated that damage to crack area 9.44%, damage to crack width 5.56%, damage to the number of holes and damage to ruts. Based on the type of handling and condition of the Girimukti-Jatimulya road section which is divided into 9 segments, segments 1, 3, 4, 7, 8, and 9 with the value of the road condition Good with the type of damage handling is enough with routine maintenance, For segment 2 the value of the road condition is medium with the type of damage handling is using periodic maintenance that must be considered, while for segments 5 and 6 with the value of the road, the condition is lightly damaged so that the type of damage handling is by road rehabilitation.